Adopting fuzzy multi-criteria decision-making ranking approach ensuring connected topology in industrial wireless sensor networks - Nandan, Anvita; Snigdh, Itu (Soft computing (Berlin, Germany), 2025)
In wireless sensor networks (WSNs), topology control aims to optimize the network structure to improve its performance and is a significant issue especially in mesh connected networks. As Industrial Wireless sensor networks (IWSNs) adopt a mesh-based strategy for communication, a connected topology and its maintenance is necessary. Therefore, identifying candidate nodes and reconfiguration under congestion and failure for reliable connection becomes important. A rank-based mechanism appears a viable solution to identify next best candidates to establish the connections among the nodes in the event of network disruption. As a solution, we propose adoption of MCDM (Multi-Criteria Decision-Making) based approach to compute the ranks among the sensor nodes when subject to varied constraints. Our paper compares and analyses the ranking of a node by using two methods, Analytical hierarchy Process (AHP) Weighted TOPSIS (Technique for Order Performance by Similarity to Ideal Solution) and FUZZY TOPSIS. A novel application of the rank-based strategy to determine the connection between the nodes for achieving a network with lower energy consumption and better connectivity for IWSNs is presented. On comparison with standard topology control algorithms, like connected dominating set (CDS) and articulation point strategy our results confirm that the topology formed through our ranking method achieves lower energy consumption in communication and better connectivity probability among the nodes. Further, we also observe performance of the network when subject to obstacles in the line-of-sight communication typical of IWSNs and our approach performs better in this case too.